2012
DOI: 10.1210/jc.2011-3419
|View full text |Cite
|
Sign up to set email alerts
|

Serum Sclerostin and Risk of Hip Fracture in Older Caucasian Women

Abstract: We conclude that higher serum sclerostin levels are associated with a greater risk of hip fractures in older women. In addition, the risk of hip fracture is amplified when high sclerostin levels are combined with lower BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
73
5
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 20 publications
10
73
5
2
Order By: Relevance
“…Fracture risks determined annually remained significant, indicating that risk was maintained over the entire study period. Our study is consistent with the most recent and only report describing higher serum sclerostin levels associated with a greater risk of hip fractures in older women (a case-cohort study of 228 women with incident hip fractures versus 227 women without fracture) (24) but our study contrasts with another recent study by Garnero and colleagues (25) who examined 572 postmenopausal women of the OFELY cohort in which a single measurement of sclerostin levels did not predict the risk of all fractures, although the study may lack statistical power to detect a modest observed association. Such differences are most likely because of differences in the methods used for sclerostin measurement and/or in the selection criteria as well as the mean age of the women examined, together with the size of the population and types of ORFs assessed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Fracture risks determined annually remained significant, indicating that risk was maintained over the entire study period. Our study is consistent with the most recent and only report describing higher serum sclerostin levels associated with a greater risk of hip fractures in older women (a case-cohort study of 228 women with incident hip fractures versus 227 women without fracture) (24) but our study contrasts with another recent study by Garnero and colleagues (25) who examined 572 postmenopausal women of the OFELY cohort in which a single measurement of sclerostin levels did not predict the risk of all fractures, although the study may lack statistical power to detect a modest observed association. Such differences are most likely because of differences in the methods used for sclerostin measurement and/or in the selection criteria as well as the mean age of the women examined, together with the size of the population and types of ORFs assessed.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, serum sclerostin levels in our cohort were similar to our reported results, (18) but higher than in reported studies for postmenopausal women. (23,24) This may be explained by differences among women studied in relation to bone mass content, body composition, and/or ethnicity. Also, variations in preanalytical and/or analytical factors (specificity of sclerostin assay) should not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This could be in apparent contradiction with the known impact of sclerostin on post-menopausal osteoporosis [30]. Hence, in post-menopausal women, high serum sclerostin levels predict osteoporotic fractures more than other bone makers [31,32]. Besides, Malluche et al [33] reported that baseline serum sclerostin level correlated with bone mass, but 1-year follow-up showed that high serum sclerostin predicts the loss of more bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of sclerostin leads to profound increases in bone mass in humans (13,18) and in animal models (19), whereas overexpression of sclerostin is associated with decreased mechanical strength in animal models (8). In a recent study, circulating sclerostin levels were positively associated with fracture risk in a large cohort of postmenopausal women (9). Moreover, established determinants of bone strength such as mechanical loading, parathyroid hormone, and estrogen have been shown to modulate the production and/or the secretion of sclerostin (12,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…TZDs have also been recently reported to stimulate sclerostin synthesis in vitro, suggesting an additional mechanism for the detrimental effects of TZDs on bone (6). Sclerostin is a glycoprotein synthesized in bone by osteocytes, which reduces bone formation (7,8), and serum sclerostin levels have been found to be significantly correlated with fracture risk in postmenopausal women (9). Abnormal sclerostin production may contribute to the pathogenesis of bone fragility of patients with T2DM as well as in the actions of TZDs on bone.…”
Section: Introductionmentioning
confidence: 99%